Synthesis and physicochemical characterization of nanostructured Pd/ceria‐clinoptilolite catalyst used for p‐xylene abatement from waste gas streams at low temperature. Issue 4 (20th August 2012) - Asgari, Nazli; Haghighi, Mohammad; Shafiei, Sirous
Abstract BACKGROUND: The effect of Pd loading, xylene concentration and GHSV on xylene oxidation was tested over Pd/CeO2(30%)‐clinoptilolite nanocatalysts at low temperatures. The catalysts were prepared by acid treatment of clinoptilolite, followed by the incipient wetness method of synthesized ceria and modified clinoptilolite in PdCl2 solution. The synthesized nanocatalysts were characterized by XRD, FESEM, EDAX, TEM, BET, FTIR and TG‐DTG analysis. RESULTS: The XRD patterns confirmed the formation of crystalline ceria with an average crystallite size of 11.8 nm. FESEM images showed nanostructures in cavities of natural zeolite, brought about by ceria incorporation and acid activation. TEM analysis showed high dispersion of Pd with a size distribution between 6.6 and 36.7 nm. The quantitative analysis showed that the specific surface area of Pd(1%)/CeO2(30%)‐clinoptilolite was 77 m2 g−1. The results showed that Pd(1%)/CeO2(30%)‐clinoptilolite is the most appropriate catalyst, with the conversion more than 90% at 275 °C. CONCLUSIONS: Experimental results established effective performance and durability for the catalysts. As a result, clinoptilolite modification and ceria incorporation significantly altered the samples' morphology at nanoscale, improving the structure of composites and distribution of noble metals. A reaction path was suggested based on the adsorption‐migration of species to reveal the mechanism of p‐xylene oxidation over nanocatalysts. © 2012 Society of Chemical Industry